Response of Symptomatic Persistent Chronic Disseminated Candidiasis to Corticosteroid Therapy in Immunosuppressed Pediatric Patients: Case Study and Review of the Literature. Issue 7 (July 2018) - Shkalim-Zemer, Vered; Levi, Itzhak; Fischer, Salvador; Tamary, Hannah; Yakobovich, Joanne; Avrahami, Gali; Gilad, Gil; Elitzur, Sara; Yaniv, Isaac; Elhasid, Ronit; Manistersky, Michal; Shalit, Itamar
Abstract : Background: Chronic disseminated candidiasis (CDC) is a severe invasive fungal infection principally observed during neutrophil recovery in patients with acute leukemia treated with intensive chemotherapy. Its pathophysiology remains unclear. We describe the management of 6 children with symptomatic CDC who did not respond to antifungal therapy. Methods: The databases of the hematology–oncology departments of 2 tertiary pediatric medical centers were searched for all patients diagnosed with CDC from 2003 to 2015, who responded to corticosteroids after failing antifungal therapy. Clinical, laboratory and radiologic data were collected. Results: Six patients (3 women, 3 men; 9–18 years of age) met the study criteria. Underlying diseases were acute lymphoblastic leukemia (n = 3) and large B-cell lymphoma, acute myeloid leukemia and severe aplastic anemia (n = 1 each). Presenting symptoms/signs of CDC were fever in all cases, with abdominal or chest pain, and/or mucositis. Candida infection was identified in blood cultures in 4 patients and in bronchoalveolar lavage fluid in one. In the absence of response to antifungal agents (4–50 days from CDC diagnosis), prednisone 2 mg/kg/day or equivalent was administered. CDC-attributable clinical symptoms resolved in 4 patients within 6–19 days; one patient required an additional nonsteroidal anti-inflammatory agent. Abnormalities on imaging decreased or disappeared within 5 months to 2 years in 4 patients. Conclusions: In children with persistent symptomatic CDC, despite adequate antifungal therapy, administration of corticosteroids may yield rapid resolution of symptoms and decreased inflammatory markers. In patients who do not respond to steroids, the addition of a nonsteroidal anti-inflammatory drug should be considered.